Faktor-Faktor yang Memengaruhi Preferensi Masyarakat Muslim di Kota Bandung Dalam Memilih Hotel Syariah - Cupian, Cupian; Melita, Virka; Laili, Vanny; Meilasari, Kintan; Noven, Sarah Annisa (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
Islam emphasizes the values of outward nobility as a foundation in business practices for Muslim business people. However, not a few business people tend to practice business that is detrimental to others even to the environment. This study reviews the principles in business practice from an Islamic perspective. Sharia hotels are an attractive offer in order to improve the moral quality and character of the noble Indonesian nation. Sharia hotels are still a foreign word, especially for ordinary people. To find out whether Islamic hotels are different from conventional hotels, this study raises the formulation of the problem, namely: 1. How do marketing mix factors 7P (Product), Price (Promotion), Promotion (Place), Place (Marketing channel), People of participant ( people), Process (Physical), and Physical evidence (physical evidence) of the preferences of Muslim communities in the city of Bandung in choosing a sharia hotel? 2. How does the knowledge factor towards the preferences of the Muslim community in Bandung in choosing a sharia hotel? 3. What is the factor of religiosity towards Muslim community preferences in Bandung in choosing sharia hotels? 4. How do hotel image factors affect Muslim community preferences in Bandung in choosing sharia hotels? 5. What are the accessibility factors to Muslim community preferences in Bandung in choosing sharia hotels?The purpose of this study is to analyze the factors that influence the preferences of Muslim communities in the city of Bandung in choosing sharia hotels as a place to stay.